MiR‐101 promotes pain hypersensitivity in rats with chronic constriction injury via the MKP‐1 mediated MAPK pathway - Qiu, Shuang; Liu, Benjuan; Mo, Yanshuai; Wang, Xueqin; Zhong, Lina; Han, Xiao; Mi, Fuli (Journal of cellular and molecular medicine, 2020)
This study was performed to characterize the effect of microRNA‐101 (miR‐101) on the pain hypersensitivity in CCI rat models with the involvement of mitogen‐activated protein kinase phosphatase 1 (MKP‐1) in spinal cord microglial cells. The mechanical withdrawal threshold (MWT) and thermal withdrawal latency (TWL) in the developed CCI models were determined to assess the hypersensitivity of rats to mechanical stimulation and thermal pain. To assess inflammation, the levels of interleukin (IL)‐1β, IL‐6 and tumour necrosis factor‐α (TNF‐α) in the spinal dorsal horns of CCI rats and lipopolysaccharide (LPS)‐activated microglial cells were examined. miR‐101 and MKP‐1 gain‐ and loss‐of‐function experiments were conducted in in vivo and in vitro settings to examine the roles of miR‐101 and MKP‐1 in CCI hypersensitivity and inflammation. The results showed that miR‐101 was highly expressed in the spinal dorsal horn and microglial cells of CCI rat models. Furthermore, overexpression of miR‐101 promoted the pain hypersensitivity in CCI rat models by reducing MWT and TWL. The overexpression of miR‐101 also promoted inflammation in LPS‐exposed microglial cells, as indicated by increased levels of IL‐1β, IL‐6 and TNF‐α. MiR‐101 was shown to target MKP‐1, inhibiting its expression. Moreover, miR‐101 promoted pain hypersensitivity in CCI rat models by inhibiting MKP‐1 expression and activating the mitogen‐activated protein kinase (MAPK) signalling pathway. Taken together, miR‐101 could potentially promote hypersensitivity and inflammatory response of microglial cells and aggravate neuropathic pain in CCI rat models by inhibiting MKP‐1 in the MAPK signalling pathway.